2019
DOI: 10.3390/s19081824
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of Aircraft Wing Panels Using Unmanned Aerial Vehicles

Abstract: In large civil aircraft manufacturing, a time-consuming post-production process is the non-destructive inspection of wing panels. This work aims to address this challenge and improve the defects’ detection by performing automated aerial inspection using a small off-the-shelf multirotor. The UAV is equipped with a wide field-of-view camera and an ultraviolet torch for implementing non-invasive imaging inspection. In particular, the UAV is programmed to perform the complete mission and stream video, in real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the field of SHM, they have been successfully applied extensively (see, e.g., [26][27][28][29][30][31][32]). In particular, DIC techniques have been successfully use for inspection of bridges [33] and of other civil engineering structures [34] in both concrete and asphalt [35], as well as for mechanical components and machines, even by means of unmanned aerial vehicle video acquisitions [36,37]. An exhaustive review of several DIC techniques can be found in [38]; interested audience may find useful information, especially for the applications of DIC techniques in aerospace and civil engineering instances, in [39].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of SHM, they have been successfully applied extensively (see, e.g., [26][27][28][29][30][31][32]). In particular, DIC techniques have been successfully use for inspection of bridges [33] and of other civil engineering structures [34] in both concrete and asphalt [35], as well as for mechanical components and machines, even by means of unmanned aerial vehicle video acquisitions [36,37]. An exhaustive review of several DIC techniques can be found in [38]; interested audience may find useful information, especially for the applications of DIC techniques in aerospace and civil engineering instances, in [39].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, development cycles can be shortened significantly with automatic code generation. SCADE from Esterel Technologies, Simulink [38] from Mathworks, and many other tools like Rodin have built-in code generators that can transform behavior models into equivalent C code. The code generated from the formal model ensures traceability from the source code to the behavior model.…”
Section: Formal Analysis Of Source Codementioning
confidence: 99%
“…The key challenge of all the above automated techniques is developing defect detection algorithms that are able to perform with accuracy and repeatability. Several attempts have been made and most of them can be divided into the following two categories: the ones that use more traditional image processing techniques [5,[16][17][18] and the ones that use machine learning [19][20][21][22][23][24]. In the first category, image features such as convexity or signal intensity [5] are used.…”
Section: Introductionmentioning
confidence: 99%
“…In the first category, image features such as convexity or signal intensity [5] are used. In [18], the authors proposed a method using histogram comparisons or structural similarity. In addition, in [16,17], the authors proposed the use of neural networks trained on feature vectors extracted from contourlet transform.…”
Section: Introductionmentioning
confidence: 99%